Analysis Of Leading And Potential Economic Sectors In Bangli Regency To Drive Economic Growth As Implementation Efforts Of The Kerthi Bali Economic Roadmap - Gede Agus Dian Maha Yoga; Putu Yudy Wijaya; Ni Wayan Wina Premayani; Luh Nik Oktarini; Gusti Alit Suputra (Jurnal Ekonomi, 2024)
The aim of this research is to examine the economic potential of Bangli Regency from the perspective of sectoral distribution towards economic growth during the period 2019-2023This research employs a quantitative descriptive approach utilizing three analytical methods: LQ-DLQ, Klassen typology, and shift-share analysis. Primary data sources consist of secondary data from the Central Statistics Agency (BPS) of Bali Province and Bangli Regency, complemented by primary data gathered from relevant informants. The study observes the period from 2019 to 2023 to examine the structural changes and sectoral distribution of the economy before and after the COVID-19 pandemic, using GRDP as an indicator. Economic sectors in Bangli Regency are categorized into 17 sectors, evaluated through LQ-DLQ methodology to identify leading sectors and potential economic bases. Findings are interpreted using Klassen typology and shift-share analysis to assess regional economic growth performance and competitiveness. Based on the empirical study conducted, the research findings reveal several key insights into the economic sectors of Bangli Regency from 2019 to 2023. The study identifies significant potential in both basic and non-basic sectors. Basic economic sectors with notable potential include agriculture, forestry, and fisheries; mining and quarrying; manufacturing industry; wholesale and retail trade; motor vehicle and motorcycle repair; government administration, defense, and mandatory social security; as well as other services. Non-basic sectors showing promise encompass electricity and gas supply; water supply, waste management, recycling; construction; transportation and warehousing; accommodation and food services; information and communication; financial and insurance activities; real estate; and corporate services. Furthermore, the research categorizes economic sectors into those demonstrating fast growth and competitiveness versus those with slower growth but still competitive. Sectors exhibiting rapid growth and competitiveness include manufacturing industry; water supply, waste management, recycling; construction; wholesale and retail trade, motor vehicle and motorcycle repair; information and communication; real estate; health and social activities; and other services. Conversely, sectors with slower growth yet competitive aspects comprise electricity and gas supply; transportation and warehousing; accommodation and food services; and corporate services. Moreover, sectors experiencing rapid growth but lacking competitiveness consist of agriculture, forestry, and fisheries; mining and quarrying; government administration, defense, and mandatory social security; education services; and financial and insurance activities. These insights provide a comprehensive understanding of how different economic sectors contribute to the dynamic economic landscape of Bangli Regency, guiding future policy directions and development strategies for sustainable economic growth and local community welfare enhancement.